1998
DOI: 10.1038/bjc.1998.50
|View full text |Cite
|
Sign up to set email alerts
|

Are serial measurements of CA19-9 useful in predicting response to chemotherapy in patients with inoperable adenocarcinoma of the pancreas?

Abstract: Summary Thirty-nine patients with inoperable adenocarcinoma of the pancreas were studied (27 male, 12 female; median age 60 years, range 39-75 years). All patients received chemotherapy with continuous infusion 5-fluorouracil with intravenous bolus epirubicin followed by cisplatin, repeated every 21 days for a total of six cycles and were evaluable for response. Serum CAl 9-9 concentrations were obtained at baseline and before each cycle. A rise or fall in the tumour marker was defined as a greater than 15% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 18 publications
0
37
0
1
Order By: Relevance
“…Previous studies have demonstrated a prognostic role for pretreatment CA19-9 in patients receiving radiotherapy or undergoing pancreatic resection (Glenn et al, 1988). Although a small number of papers have described a fall in CA19-9 to be an independent prognostic variable for survival (Gogas et al, 1998;Saad et al, 2002;Stemmler et al, 2003;Ziske et al, 2003), there have been surprisingly few studies investigating the use of baseline CA19-9 in predicting survival for patients with inoperable pancreatic cancer who undergo systemic chemotherapy. Halm et al (2000) reported the survival of 43 consecutive patients with advanced pancreatic cancer treated with single-agent gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated a prognostic role for pretreatment CA19-9 in patients receiving radiotherapy or undergoing pancreatic resection (Glenn et al, 1988). Although a small number of papers have described a fall in CA19-9 to be an independent prognostic variable for survival (Gogas et al, 1998;Saad et al, 2002;Stemmler et al, 2003;Ziske et al, 2003), there have been surprisingly few studies investigating the use of baseline CA19-9 in predicting survival for patients with inoperable pancreatic cancer who undergo systemic chemotherapy. Halm et al (2000) reported the survival of 43 consecutive patients with advanced pancreatic cancer treated with single-agent gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a small number of publications suggesting that the tumour marker CA19-9 is an important prognostic variable (Gogas et al, 1998;Halm et al, 2000;Saad et al, 2002;Stemmler et al, 2003;Ziske et al, 2003), none of the large published randomised studies of chemotherapy to date have reported baseline CA19-9 levels.…”
mentioning
confidence: 99%
“…Whether serum CA 19-9 levels can be used as a surrogate marker of response to chemotherapy has been studied in a variety of clinical settings [41,44,[53][54][55][56][57][58][59][60][61][62][63][64]. Willett et al measured CA 19-9 serum levels in 42 resectable pancreatic cancer patients receiving neoadjuvant treatment with 5-flourouracil and external beam radiation prior to planned pancreaticoduodenectomy.…”
Section: Ca 19-9 Serum Levels As a Biomarker For Chemotherapy Responsmentioning
confidence: 99%
“…Nearly all studies have demonstrated that a treatment related decline in CA 19-9 serum levels is associated with prolonged survival and is an independent predictor of overall survival [41,44,[53][54][55][56][57][58][59][60][61][62][63][64] (Table 5). Reni et al compared basal CA 19-9 serum levels in 247 advanced pancreatic cancer patients enrolled in five consecutive chemotherapy trials (G, gemcitabine; PEFG, cisplatin, epirubicin, 5-fluorouracil, and gemcitabine; PDXG, cisplatin, docetaxel, capecitabine, and gemcitabine) [60].…”
Section: Ca 19-9 Serum Levels As a Biomarker For Chemotherapy Responsmentioning
confidence: 99%
“…Several studies have reported a close correlation between CA19-9 kinetics and therapy response, even if they used different definitions of CA19-9 decrease as criterion for therapy efficacy (6,(26)(27)(28)(29)(30)(31). Stemmler et al demonstrated CA19-9 decreases during chemotherapyindependent from their degree -were associated with longer survival, whereas increasing levels were linked with poor prognosis (31).…”
Section: Introductionmentioning
confidence: 99%